Knowledge transfer, Learning and Organizational Capabilities in an inter-organizational software project - Ayres, Rosane Maria Soligo de Mello; Popadiuk, Silvio (Organizações & Sociedade, 2016)
The aim of this work is to describe how learning and knowledge transfer mechanisms based on knowledge articulation and codification contribute to the development of organizational capabilities in software. The study focuses on client-specific and process capabilities. Results were obtained through a case study involving two partner companies in an inter-organizational project to develop an integrated information management and technology system. Evidence revealed investment and organizational efforts focused on knowledge articulation practices and activities to develop client-specific capabilities, as well as knowledge codification practices and activities to develop process capabilities. We also identified three factors that influenced software professionals’ choice of the respective mechanisms (knowledge articulation and codification) namely: the sharing context, absorptive capacity and task complexity.